PELATIHAN PEMBUATAN PUPUK ORGANIK CAIR DARI TUMBUHAN AIR DI KAMPUNG YOBOI-SENTANI, PAPUA - Lisye Iriana Zebua; I Made Budi; Henderitte L. Ohee; Diki Markus Lukas Doirebo; Peter Youngren Samberi; Andika Vulvian Al Rasyid (LP2M Universitas Hasanuddin, 2023)
Hydrilla verticillata, Pistia stratiotes (Apu-apu), and Eichhornia crassipes (eceng gondok) thrive around the waters of Kampung Yoboi and Lake Sentani. Currently, the three types of aquatic plants have become weeds and are causing problems in the lake's water environment, especially the problem of water transportation between villages. This community service activity aims to train the people of Kampung Yoboi to utilise the aquatic plants Hydrilla verticillata, Pistia stratiotes (Apu-apu), and Eichhornia crassipes (water hyacinth) in liquid organic fertiliser (POC) using a fermentation technique with EM-4. The target of the training activities is Sunday school caregivers. The training activities were carried out for two meetings. Based on the pre-test results, 80% of the mothers understood the benefits of fertiliser, but 80% did not understand the making of POC. The method used in the training consists of three stages, namely lecture, discussion, and practice. The result of the training is that Sunday school caretakers have understood how to make POC from aquatic plant materials in their environment using the EM-4 fermentation technique. This activity has also changed the paradigm of the people of Kampung Yoboi regarding Hydrilla verticillata, Pistia stratiotes, and Eichhornia crassipes, which were considered weeds, into useful plants. — Tumbuhan air Hydrilla verticillata, Pistia stratiotes (Apu-apu), dan Eichhornia crassipes (Eceng gondok) tumbuh subur di sekitar perairan Kampung Yoboi, Danau Sentani. Saat ini ketiga jenis tumbuhan air tersebut telah menjadi gulma dan menimbulkan masalah di lingkungan air danau, terutama masalah transportasi air antar kampung. Kegiatan pengabdian masyarakat ini bertujuan untuk melatih masyarakat Kampung Yoboi untuk memanfaatkan tumbuhan air Hydrilla verticillata, Pistia stratiotes (Apu-apu), dan Eichhornia crassipes (Eceng gondok) menjadi pupuk organik cair (POC) menggunakan teknik fermentasi dengan EM-4. Sarasaran kegiatan pelatihan adalah ibu-ibu pengasuh Sekolah Minggu. Kegiatan pelatihan dilaksanakan selama dua kali pertemuan. Berdasarkan hasil pre-test 80% ibu-ibu belum memahami manfaat pupuk dan belum memahami pembuatan POC. Metode yang digunakan dalam pelatihan terdiri dari tiga tahap yaitu ceramah, diskusi, dan praktik. Hasil dari pelatihan adalah, ibu-ibu pengasuh Sekolah Minggu telah mengerti dan memahami cara membuat POC dari bahan tumbuhan air yang ada di sekitar lingkungan mereka dengan teknik fermentasi EM-4. Melalui kegiatan ini juga telah mengubah paradigma masyarakat Kampung Yoboi mengenai Hydrilla verticillata, Pistia stratiotes, dan Eichhornia crassipes yang dianggap sebagai gulma, menjadi tumbuhan yang bermanfaat.